2022
DOI: 10.1007/s10639-021-10830-7
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive learning in university students’ opinions: Cross-border research

Abstract: Contemporary education is often based on using e-learning courses, which have become a popular means of delivering didactic material to students. Among the main advantages mentioned is the potential possibility of creating individual ways of learning and teaching. The purpose of this article is to provide a description of the various approaches to adaptive learning, to present the comparative research results of a Polish-Ukrainian study, as well as to highlight the options offered by LMS Moodle (Modular object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 25 publications
(30 reference statements)
0
7
0
Order By: Relevance
“…To fully exploit the didactic usefulness of ICT, it is required to identify the learning objectives and match the digital tools to the achievement of those objectives (Smyrnova-Trybulska, Morze & Varchenko-Trotsenko, 2022). Consequently, as different subject areas have different learning objectives and outcomes, the way ICT should be applied in the classroom and the type of resources that teachers should use depends on the subject area (Antón-Sancho, Vergara, Fernández-Arias & Ariza-Echeverri, 2022c).…”
Section: Introductionmentioning
confidence: 99%
“…To fully exploit the didactic usefulness of ICT, it is required to identify the learning objectives and match the digital tools to the achievement of those objectives (Smyrnova-Trybulska, Morze & Varchenko-Trotsenko, 2022). Consequently, as different subject areas have different learning objectives and outcomes, the way ICT should be applied in the classroom and the type of resources that teachers should use depends on the subject area (Antón-Sancho, Vergara, Fernández-Arias & Ariza-Echeverri, 2022c).…”
Section: Introductionmentioning
confidence: 99%
“…In the last year, 24,800 active platform users have been registered. The majority of academic teachers successfully participated in teacher training courses in personal or online mode (20 h total) and now hold certificates as tutors and as e‐learning course authors in the use of the Moodle system (Smyrnova‐Trybulska et al., 2022). The number of active courses on all faculty platforms (i.e.…”
Section: Research Results and Discussionmentioning
confidence: 99%
“…The work by [20], in the purpose of this article, is aimed at providing a description of various approaches to adaptive learning, and as a result, in the system Moodle elearning courses, as well as Polish and Ukrainian students by using the Google Suite for Ms teams conducted for students in synchronous and asynchronous modes of the results arrived at, and also achieved the lessons they provide the benefits of this technology, in this context, when this value is combined with the values of the research, it is seen that the audience in the study is trained with google meet technology, and it is concluded that moodle applications benefit their courses synchronously within the system they use, it can be said that they benefit students in both values in this context.…”
Section: Discussionmentioning
confidence: 99%